Comparative Toxicity of Interferon Beta-1a Impurities of Heavy Metal Ions - Dmitriy Berillo (Medicina, 2022)
Background and Objectives: Providing a proper quality control of drugs is essential for efficient treatment of various diseases minimizing the possible side effects of pharmaceutical active substances and potential impurities. Recent in vitro and in vivo studies have shown that certain heavy metalloids and metals interfere with protein folding of nascent proteins in cells and their biological function can be altered. It is unknown whether the drug impurities including heavy metals may affect the tertiary protein structure. Materials and Methods: ReciGen and Rebif are pharmaceutical interferon beta-1a (IFNβ-1a) contained in preparations that are used for parenteral administration. Heavy metal impurities of these samples have been studied by gel electrophoresis, Fourier-transform infrared spectroscopy (FTIR) and inductively coupled plasma mass spectrometry analysis (ICP MS). The concentration of heavy metals including mercury, arsenic, nickel, chromium, iron, and aluminum did not exceed permitted levels established by International Council for Harmonisation guideline for elemental impurities. Results: The ICP MS analysis revealed the presence of heavy metals, moreover zeta potential was significantly different for IFNβ-1a, which can be an indirect indication of the difference in composition of ReciGen and Rebif samples, respectively. FTIR analysis revealed very similar amide I and II bonds at 1654 and 1560 cm−1 attributed to the peptide absorption peaks of IFNβ-1a in Rebif and ReciGen. Conclusions: It was hypothesized that the IFNβ-1a complex binds heavy metals affecting the tertiary protein structure and may lead to some side effects of drug administration. Further testing of IFNβ-1a bioequivalence for parenteral application is necessary.